A method for preparing anode material for electrocatalytic degradation of tetracycline wastewater
By forming a Sm3Co5O12-xSex film layer on the surface of the foam copper matrix and loading [Pb(CO)4]Se nanocrystals, an efficient anode material was prepared, which solved the problem of poor performance of anode material in tetracycline wastewater treatment in the prior art. Achieve efficient and stable electrocatalytic degradation effect.
Patent Information
- Application Number
- CN202410890418.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-04
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-07-04
AI Technical Summary
The existing electrochemical catalytic oxidation technology is used in tetracycline wastewater treatment. The electrocatalytic oxidation performance of the anode material is not ideal and the repeatability stability is difficult to meet the requirements of large-scale engineering applications, which hinders the development of tetracycline wastewater treatment technology.
By forming a (Sm-Co)2O6 compound layer on the surface of the foam copper matrix, and converting it into a Sm3Co5O12-xSex film layer through a selenization replacement reaction, and then supporting [Pb(CO)4]Se nanocrystals, an excellent electrocatalytic degradation was prepared. Anode material with performance and repeatability.
This material significantly improves the degradation rate of tetracycline wastewater and the efficiency of the electrocatalytic oxidation process, inhibits side reactions, enhances the reusable stability of the anode material, and maintains efficient degradation performance under different pH environments.
Smart Images

Figure CN118724189B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of tetracycline wastewater degradation, in particular to a method for preparing a material for electrocatalytically degrading tetracycline wastewater. Background Art
[0002] At present, tetracycline antibiotics are widely used in the field of human medicine and health and livestock and poultry farming as a means of treatment and growth medicine, respectively. However, the absorption rate of tetracycline antibiotics in the human and animal digestive systems is only 20% to 70%, and about 30% to 80% is discharged into the external environment, seriously polluting the water body. In addition, the production process of tetracycline antibiotics will also produce a large amount of pharmaceutical wastewater rich in tetracycline pollutants.
[0003] The hydrogenated tetracene structure of tetracycline is highly stable. Its difficulty in self-degradation and easy enrichment not only increase bacterial resistance, but also easily cause long-term ecological toxicity hazards. At present, the treatment methods of tetracycline wastewater mainly include physicochemical treatment technology, biological treatment technology, and electrochemical oxidation degradation treatment technology. Among them, the physicochemical treatment technology and biological treatment technology have the disadvantages of low tetracycline removal rate, complicated process, easy to cause secondary pollution, and long treatment cycle. Electrochemical catalytic oxidation degradation of tetracycline wastewater treatment technology has simple equipment and process requirements, short treatment cycle, and no secondary pollution. It is an effective method for tetracycline wastewater treatment.
[0004] The electrochemical catalytic oxidation anode material determines the degradation rate and reaction rate of the electrocatalytic degradation of tetracycline. The repeated stability of the electrochemical catalytic oxidation anode material is also an important basis for the large-scale engineering application of the electrocatalytic degradation of tetracycline wastewater treatment technology. However, the electrocatalytic oxidation performance of the anode electrode materials currently used in the electrochemical catalytic oxidation degradation of tetracycline wastewater treatment is not ideal, and the repeated stability is difficult to meet the requirements of large-scale engineering production, which has become a key issue hindering the development of the electrocatalytic degradation of tetracycline wastewater treatment technology. Summary of the invention
[0005] In order to overcome the shortcomings of the prior art, the present invention provides a method for preparing an anode material for electrocatalytic degradation of tetracycline wastewater. The anode material prepared by the method has excellent electrocatalytic degradation of tetracycline wastewater treatment performance and excellent long-term stability.
[0006] The technical solution adopted by the present invention to solve its technical problem is:
[0007] The present invention provides a method for preparing an anode material for electrocatalytic degradation of tetracycline wastewater, comprising the following steps performed in sequence:
[0008] Step [1] forming a (Sm-Co)2O6 compound layer on the surface of the copper foam substrate;
[0009] Step [2] The (Sm-Co)2O6 compound layer on the surface of the copper foam substrate is converted into Sm3Co5O by selenization substitution reaction. 12-x Se x Film layer, where 1≤x≤4;
[0010] Step [3] Sm3Co5O on the surface of the copper foam substrate 12-x Se x [Pb(CO)4]Se nanocrystals are loaded on the film layer to finally obtain the anode material.
[0011] Preferably, the step [1] specifically includes the following operations:
[0012] a1. Add samarium tricyclopentadienide, samarium sulfate and didodecylamine to 3,5-dimethylaniline and mix well to form an additive solution; add cobalt porphyrin, cobalt oxalate and sodium ethoxide to deionized water and mix well to form a base solution; add a certain amount of the additive solution to the base solution and mix well to form an emulsified Sm-Co co-deposition solution;
[0013] a2. The copper foam is immersed in the Sm-Co co-deposition solution and used as a cathode, stainless steel is used as an anode, and electrodeposition is performed at room temperature to obtain a copper foam having a Sm-Co co-deposition layer formed on the surface, recorded as intermediate A;
[0014] a3. Sodium acetate, sodium ferric ethylenediaminetetraacetate and nitric acid with a mass fraction concentration of 69% are added to deionized water to form an oxidizing solution, and the intermediate A is immersed in the oxidizing solution for 1.5 to 3 hours at room temperature to obtain a foamed copper with a (Sm-Co)2O6 compound layer formed on the surface, which is recorded as intermediate B.
[0015] Preferably, the concentration of samarium tricyclopentadienide in the additive solution in step a1 is 105g / L-140g / L, the concentration of samarium sulfate is 270g / L-320g / L, and the concentration of didodecylamine is 30g / L-60g / L; the concentration of cobalt porphyrin in the base solution is 60g / L-110g / L, the concentration of cobalt oxalate is 160g / L-280g / L, and the concentration of sodium ethoxide is 10g / L-70g / L; the volume ratio between the additive solution and the base solution of the Sm-Co co-deposition solution is 1-3:5-8.
[0016] Preferably, in step a2, the weight of the copper foam immersed in each liter of the Sm-Co co-deposition solution is 150-210 g; the voltage of the electrodeposition is a constant voltage of 1.8 to 2.5 V, and the electrodeposition time is 8 to 25 minutes.
[0017] Preferably, the sodium acetate concentration of the oxidizing solution in step a3 is 20g / L-40g / L, the sodium ferric ethylenediaminetetraacetate concentration is 60g / L-90g / L, and the mass percentage concentration of nitric acid is 1%-5%; the weight of the intermediate A immersed in each liter of the oxidizing solution is 40-80g.
[0018] Preferably, the specific operations of step [2] are:
[0019] The intermediate B is placed in an atmosphere protection furnace, and a certain amount of selenious acid and calcium selenide are added to the furnace, and reacted at 80-100° C. for 4-7 hours under argon atmosphere to finally obtain the intermediate C;
[0020] Preferably, the added amounts of selenous acid and calcium selenide corresponding to every 350g-850g of intermediate B are 120g-190g and 80g-210g respectively.
[0021] Preferably, the step [3] specifically includes the following operations:
[0022] c1. Dissolving tetraethyl lead, tert-butyl 3,5-dicarbonylhexanoate and selenious acid in ethanol to form an organic base liquid; adding lead sulfate to deionized water to form an inorganic additive liquid; adding a certain amount of the inorganic additive liquid to the organic base liquid to form a crystallization liquid;
[0023] c2. Immersing the intermediate C into the crystallization solution, reacting in a reactor at 40-75° C. for 12-16 hours, and finally obtaining the anode material.
[0024] Preferably, in step c1, the tetraethyl lead concentration of the organic base liquid is 140 mL / L-290 mL / L, the tert-butyl 3,5-dicarbonylhexanoate concentration is 420 g / L-580 g / L, and the selenious acid concentration is 160 g / L-190 g / L; the lead sulfate concentration of the inorganic additive liquid is 100 g / L-130 g / L; and the volume ratio between the organic base liquid and the inorganic additive liquid of the crystallization liquid is 1-2:3-5.
[0025] Preferably, in step c2, the weight of the intermediate C immersed in each liter of the crystallization solution is 220-250 g.
[0026] The positive effect of the present invention is as follows: the anode material (foam copper-based Sm3Co5O 12-x Se x The film is loaded with [Pb(CO)4]Se nanocrystals), and its structural characteristics are: the Sm3Co5O 12- x Se x It is a garnet-type composite oxide (such as Figure 2), where the samarium ions are located in Sm3Co5O 12-x Se x The dodecahedral gap of Sm3Co5O 12-x Se x The octahedral gap and tetrahedral gap are surrounded by oxygen atoms and selenium atoms; nanocrystalline [Pb(CO)4]Se is a complex with lead ion as the central ion and carbonyl as the ligand, such as Figure 3 As shown, the ligand ion [Pb(CO)4] 2+ It has a regular tetrahedral structure, with the lead ion located at the center of mass of the regular tetrahedron and the carbonyl group located at the four vertices of the regular tetrahedron. The ligand ion forms a [Pb(CO)4]Se coordination compound with the selenium ion. Based on the above structural characteristics, nanocrystalline [Pb(CO)4]Se can significantly increase the oxygen evolution overpotential in the electrocatalytic oxidation of tetracycline wastewater degradation, and can effectively inhibit the occurrence of oxygen evolution side reactions. 2+ The cobalt ions can also reduce the electrochemical oxidation removal barrier of tetracycline benzene ring; Sm3Co5O 12-x Se x The samarium ion has 4f electrons, a large ion radius, and high oxygen conductivity, which can effectively promote the generation of a large number of hydroxyl radicals and the formation of cobalt peroxides in the electrocatalytic oxidation of tetracycline wastewater degradation, and can significantly accelerate the kinetic process of electrocatalytic oxidation and destruction of the benzene ring in the tetracycline structure. 12-x Se x The layer-loaded [Pb(CO)4]Se nanocrystalline anode material has excellent tetracycline wastewater degradation performance (high degradation rate) and excellent repeated stable electrocatalytic degradation performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a schematic diagram of the preparation process of the anode material of the present invention;
[0028] Figure 2 The Sm3Co5O 12-x Se x Schematic diagram of the structure;
[0029] Figure 3 is a schematic diagram of the structure of the [Pb(CO)4]Se nanocrystal of the present invention;
[0030] Figure 4a is a comparison chart of tetracycline degradation rates in Example 1 of the present invention under different pH simulation environments;
[0031] Figure 4b This is a comparison chart of tetracycline degradation rates in comparative example 1 of the present invention under different pH simulated environments;
[0032] Figure 4c This is a comparison chart of tetracycline degradation rates in comparative example 2 of the present invention under different pH simulated environments;
[0033] Figure 5a is a graph showing the relationship between the number of uses and the degradation rate of tetracycline in Example 1 of the present invention under different pH simulated environments;
[0034] Figure 5b is a graph showing the relationship between the number of uses and the degradation rate of tetracycline in Comparative Example 1 of the present invention under different pH simulated environments;
[0035] Figure 5c 3 is a graph showing the relationship between the number of uses of comparative example 2 of the present invention and the degradation rate of tetracycline under different pH simulated environments. DETAILED DESCRIPTION
[0036] Reference Figure 1 The present invention provides a method for preparing an anode material for electrocatalytic degradation of tetracycline wastewater, comprising the following steps performed in sequence:
[0037] Step [1] forms a (Sm-Co)2O6 compound layer on the surface of the copper foam substrate, specifically comprising the following operations:
[0038] a1. Add samarium tricyclopentadienide, samarium sulfate and didodecylamine to 3,5-dimethylaniline and mix them evenly to form an additive solution having a samarium tricyclopentadienide concentration of 105 g / L-140 g / L, a samarium sulfate concentration of 270 g / L-320 g / L and a didodecylamine concentration of 30 g / L-60 g / L; add cobalt porphyrin, cobalt oxalate and sodium ethoxide to deionized water and mix them evenly to form a base solution having a cobalt porphyrin concentration of 60 g / L-110 g / L, a cobalt oxalate concentration of 160 g / L-280 g / L and a sodium ethoxide concentration of 10 g / L-70 g / L; add the additive solution to the base solution in a volume ratio of 1 to 3:5 to 8 and mix them evenly to form a water / organic reagent emulsion type Sm-Co co-deposition solution;
[0039] a2. Immersing the copper foam in the Sm-Co co-deposition solution (the weight of the copper foam immersed in each liter of the Sm-Co co-deposition solution is 150-210 g) and using it as a cathode, stainless steel as an anode, and performing electrodeposition at room temperature, wherein the electrodeposition voltage is a constant voltage of 1.8 to 2.5 V, and the electrodeposition time is 8 to 25 minutes to obtain a copper foam having a Sm-Co co-deposition layer formed on the surface, recorded as intermediate A;
[0040] a3. Sodium acetate, sodium ferric ethylenediaminetetraacetate and nitric acid with a mass fraction concentration of 69% are added to deionized water to form an oxidizing solution with a sodium acetate concentration of 20g / L-40g / L, a sodium ferric ethylenediaminetetraacetate concentration of 60g / L-90g / L, and a nitric acid mass percentage concentration of 1%-5%, and the intermediate A is immersed in the oxidizing solution (the weight of the intermediate A immersed in each liter of the oxidizing solution is 40-80g), and immersed at room temperature for 1.5 to 3 hours to obtain a foamed copper with a (Sm-Co)2O6 compound layer formed on the surface, which is recorded as intermediate B.
[0041] Step [2] The (Sm-Co)2O6 compound layer on the surface of the copper foam substrate is converted into Sm3Co5O by selenization substitution reaction. 12-x Se x Film layer, where 1≤x≤4; the specific operation is:
[0042] 350g-850g of intermediate B is placed in an atmosphere protection furnace, and 120g-190g of selenious acid and 80g-210g of calcium selenide are added to the furnace. Under argon atmosphere, the reaction is carried out at 80-100°C for 4-7 hours to finally obtain intermediate C (with Sm3Co5O 12-x Se x Copper foam of the film layer);
[0043] Step [3] Sm3Co5O on the surface of the copper foam substrate 12-x Se x The [Pb(CO)4]Se nanocrystals are loaded on the film layer, specifically including the following operations:
[0044] c1. Tetraethyl lead, tert-butyl 3,5-dicarbonyl hexanoate and selenious acid are dissolved in ethanol to form an organic base liquid having a tetraethyl lead concentration of 140 mL / L-290 mL / L, a tert-butyl 3,5-dicarbonyl hexanoate concentration of 420 g / L-580 g / L, and a selenious acid concentration of 160 g / L-190 g / L; lead sulfate is added to deionized water to form an inorganic additive liquid having a lead sulfate concentration of 100 g / L-130 g / L; a certain amount of inorganic additive liquid is added to the organic base liquid (the volume ratio between the organic base liquid and the inorganic additive liquid is 1 to 2: 3 to 5) to form a crystallization liquid;
[0045] c2. Immerse the intermediate C in the crystallization solution (the weight of the intermediate C immersed in each liter of the crystallization solution is 220-250 g), and react in a reactor at 40-75 ° C for 12-16 hours to form Sm3Co5O on the surface of the foam copper base. 12-x Se x The film layer is loaded with [Pb(CO)4]Se nanocrystals, and finally the anode material (foam copper-based Sm3Co5O 12-x Se x layer loaded with [Pb(CO)4]Se nanocrystals).
[0046] The preferred embodiments of the present invention are described below by way of example.
[0047] Example 1
[0048] Preferred embodiment 1 of the present invention provides a method for preparing an anode material for electrocatalytic degradation of tetracycline wastewater, comprising the following steps performed in sequence:
[0049] Step [1] forms a (Sm-Co)2O6 compound layer on the surface of the copper foam substrate, specifically comprising the following operations:
[0050] a1. Add samarium tricyclopentadienide, samarium sulfate and didodecylamine to 3,5-dimethylaniline and mix well to form an additive solution having a samarium tricyclopentadienide concentration of 130 g / L, a samarium sulfate concentration of 300 g / L and a didodecylamine concentration of 50 g / L; add cobalt porphyrin, cobalt oxalate and sodium ethoxide to deionized water and mix well to form a base solution having a cobalt porphyrin concentration of 100 g / L, a cobalt oxalate concentration of 200 g / L and a sodium ethoxide concentration of 50 g / L; add the additive solution to the base solution in a volume ratio of 3:5 and mix well to form a water / organic reagent emulsion type Sm-Co co-deposition solution;
[0051] a2. The copper foam was immersed in the Sm-Co co-deposition solution (the weight of the copper foam immersed in each liter of the Sm-Co co-deposition solution was 200 g) and used as a cathode, stainless steel was used as an anode, and electrodeposition was performed at room temperature, wherein the electrodeposition voltage was a constant voltage of 2.1 V, and the electrodeposition time was 15 minutes to obtain a copper foam with a Sm-Co co-deposition layer formed on the surface, which was recorded as intermediate A;
[0052] a3. Sodium acetate, sodium ferric ethylenediaminetetraacetate and 69% nitric acid by mass are added to deionized water to form an oxidizing solution with a sodium acetate concentration of 30 g / L, an ethylenediaminetetraacetate sodium ferric concentration of 80 g / L and a nitric acid mass percentage concentration of 4%, and the intermediate A is immersed in the oxidizing solution (the weight of the intermediate A immersed in each liter of the oxidizing solution is 70 g), and immersed at room temperature for 2 hours to obtain a foamed copper with a (Sm-Co)2O6 compound layer formed on the surface, which is recorded as intermediate B.
[0053] Step [2] The (Sm-Co)2O6 compound layer on the surface of the copper foam substrate is converted into Sm3Co5O by selenization substitution reaction. 12-x Se x Film layer, where 1≤x≤4; the specific operation is:
[0054] 500g of intermediate B was placed in an atmosphere protection furnace, and 180g of selenious acid and 200g of calcium selenide were added to the furnace. The reaction was carried out at 90°C for 6 hours under argon atmosphere to finally obtain intermediate C (with Sm3Co5O 12-x Se x Copper foam of the film layer);
[0055] Step [3] Sm3Co5O on the surface of the copper foam substrate 12-x Se x The [Pb(CO)4]Se nanocrystals are loaded on the film layer, specifically including the following operations:
[0056] c1. Tetraethyl lead, tert-butyl 3,5-dicarbonyl hexanoate and selenous acid were dissolved in ethanol to form an organic base liquid having a tetraethyl lead concentration of 200 mL / L, tert-butyl 3,5-dicarbonyl hexanoate concentration of 470 g / L and selenous acid concentration of 165 g / L; lead sulfate was added to deionized water to form an inorganic additive liquid having a lead sulfate concentration of 125 g / L; a certain amount of inorganic additive liquid was added to the organic base liquid (the volume ratio between the organic base liquid and the inorganic additive liquid was 2:5) to form a crystallization liquid;
[0057] c2. The intermediate C is immersed in the crystallization solution (the weight of the intermediate C immersed in each liter of the crystallization solution is 245g), and reacted in a reactor at 70°C for 14 hours to form Sm3Co5O on the surface of the foam copper base. 12-x Se x The film layer is loaded with [Pb(CO)4]Se nanocrystals, and finally the anode material (foam copper-based Sm3Co5O 12-x Se x Layer loaded with [Pb(CO)4]Se nanocrystals), recorded as Example 1.
[0058] Comparative Example 1
[0059] This comparative example 1 provides a method for preparing a foam copper-based (Sm-Co)2O6 layer-loaded [Pb(CO)4]Se nanocrystalline material, comprising the following steps performed in sequence:
[0060] Step [1] forms a (Sm-Co)2O6 compound layer on the surface of the copper foam substrate, specifically comprising the following operations:
[0061] a1. Add samarium tricyclopentadienide, samarium sulfate and didodecylamine to 3,5-dimethylaniline and mix well to form an additive solution having a samarium tricyclopentadienide concentration of 110 g / L, a samarium sulfate concentration of 275 g / L and a didodecylamine concentration of 35 g / L; add cobalt porphyrin, cobalt oxalate and sodium ethoxide to deionized water and mix well to form a base solution having a cobalt porphyrin concentration of 70 g / L, a cobalt oxalate concentration of 180 g / L and a sodium ethoxide concentration of 20 g / L; add the additive solution to the base solution in a volume ratio of 1:5 and mix well to form a water / organic reagent emulsion type Sm-Co co-deposition solution;
[0062] a2. The copper foam was immersed in the Sm-Co co-deposition solution (the weight of the copper foam immersed in each liter of the Sm-Co co-deposition solution was 160 g) and used as a cathode, stainless steel was used as an anode, and electrodeposition was performed at room temperature, wherein the electrodeposition voltage was a constant voltage of 1.9 V, and the electrodeposition time was 10 minutes to obtain a copper foam with a Sm-Co co-deposition layer formed on the surface, which was recorded as intermediate A;
[0063] a3. Sodium acetate, sodium ferric ethylenediaminetetraacetate and 69% nitric acid by mass are added to deionized water to form an oxidizing solution with a sodium acetate concentration of 25 g / L, a sodium ferric ethylenediaminetetraacetate concentration of 70 g / L and a nitric acid mass percentage concentration of 2%, and the intermediate A is immersed in the oxidizing solution (the weight of the intermediate A immersed in each liter of the oxidizing solution is 50 g), and immersed at room temperature for 2 hours to obtain a foamed copper with a (Sm-Co)2O6 compound layer formed on the surface, which is recorded as intermediate B.
[0064] Step [2] loading [Pb(CO)4]Se nanocrystals on the (Sm-Co)2O6 compound layer on the surface of the copper foam substrate, specifically comprising the following operations:
[0065] c1. Tetraethyl lead, tert-butyl 3,5-dicarbonyl hexanoate and selenous acid were dissolved in ethanol to form an organic base solution having a tetraethyl lead concentration of 150 mL / L, a tert-butyl 3,5-dicarbonyl hexanoate concentration of 450 g / L and a selenous acid concentration of 170 g / L; lead sulfate was added to deionized water to form an inorganic additive solution having a lead sulfate concentration of 110 g / L; a certain amount of the inorganic additive solution was added to the organic base solution (the volume ratio between the organic base solution and the inorganic additive solution was 1:3) to form a crystallization solution;
[0066] c2. Immerse the intermediate B in the crystallization solution (the weight of the intermediate B immersed in each liter of the crystallization solution is 230 g), and react in a reactor at 45°C for 13 hours to load [Pb(CO)4]Se nanocrystals on the (Sm-Co)2O6 compound layer on the surface of the foam copper base, and finally obtain the foam copper-based (Sm-Co)2O6 layer loaded with [Pb(CO)4]Se nanocrystal material, which is recorded as Comparative Example 1.
[0067] Comparative Example 2
[0068] This comparative example 2 provides a foam copper-based Sm3Co5O 12-x Se x The method for preparing the material comprises the following steps performed in sequence:
[0069] Step [1] forms a (Sm-Co)2O6 compound layer on the surface of the copper foam substrate, specifically comprising the following operations:
[0070] a1. Add samarium tricyclopentadienide, samarium sulfate and didodecylamine to 3,5-dimethylaniline and mix well to form an additive solution having a samarium tricyclopentadienide concentration of 120 g / L, a samarium sulfate concentration of 290 g / L and a didodecylamine concentration of 50 g / L; add cobalt porphyrin, cobalt oxalate and sodium ethoxide to deionized water and mix well to form a base solution having a cobalt porphyrin concentration of 80 g / L, a cobalt oxalate concentration of 190 g / L and a sodium ethoxide concentration of 30 g / L; add the additive solution to the base solution in a volume ratio of 2:7 and mix well to form a water / organic reagent emulsion type Sm-Co co-deposition solution;
[0071] a2. The copper foam was immersed in the Sm-Co co-deposition solution (the weight of the copper foam immersed in each liter of the Sm-Co co-deposition solution was 160 g) and used as a cathode, stainless steel was used as an anode, and electrodeposition was performed at room temperature, wherein the electrodeposition voltage was a constant voltage of 2.0 V, and the electrodeposition time was 12 minutes to obtain a copper foam with a Sm-Co co-deposition layer formed on the surface, which was recorded as intermediate A;
[0072] a3. Sodium acetate, sodium ferric ethylenediaminetetraacetate and 69% nitric acid are added to deionized water to form an oxidizing solution with a sodium acetate concentration of 25 g / L, a sodium ferric ethylenediaminetetraacetate concentration of 70 g / L and a nitric acid mass percentage concentration of 3%, and the intermediate A is immersed in the oxidizing solution (the weight of the intermediate A immersed in each liter of the oxidizing solution is 50 g), and immersed at room temperature for 2.5 hours to obtain a foamed copper with a (Sm-Co)2O6 compound layer formed on the surface, which is recorded as intermediate B.
[0073] Step [2] The (Sm-Co)2O6 compound layer on the surface of the copper foam substrate is converted into Sm3Co5O by selenization substitution reaction.12-x Se x Film layer, where 1≤x≤4; the specific operation is:
[0074] 400 g of intermediate B was placed in an atmosphere protection furnace, and 130 g of selenious acid and 90 g of calcium selenide were added to the furnace. The reaction was carried out at 90 ° C for 6 hours under argon atmosphere to obtain a surface-formed Sm3Co5O 12-x Se x The foam copper of the film layer, that is, the foam copper-based Sm3Co5O 12-x Se x Materials are recorded as Comparative Example 2.
[0075] In order to analyze the degradation rate and repeated stability of the electrocatalytic oxidation of tetracycline wastewater in Example 1, Comparative Example 1 and Comparative Example 2, a tetracycline solution containing a tetracycline concentration of 100 mg / L, a volume of 500 ml, and a pH value of 3, 7 and 10 adjusted by sodium hydroxide and hydrochloric acid was used to simulate tetracycline wastewater, respectively, and Example 1, Comparative Example 1 and Comparative Example 2 were used as anode electrodes, stainless steel was used as auxiliary electrodes, and saturated calomel electrode was used as reference electrodes. Electrochemical catalytic tests were carried out under constant current I = 0.1A conditions, and samples were taken once every 10 minutes until 200 minutes, and the tetracycline concentration was analyzed by high performance liquid chromatography to calculate the degradation rate. Under the same electrocatalytic oxidation degradation conditions, the tetracycline degradation rates of the simulated tetracycline wastewater corresponding to Example 1, Comparative Example 1 and Comparative Example 2 with different usage times were measured to analyze the electrocatalytic oxidation repeated stability of the anode materials in Example 1, Comparative Example 1 and Comparative Example 2.
[0076] In the simulated tetracycline wastewater environment with pH values of 3, 7 and 10, the tetracycline degradation rates corresponding to Example 1, Comparative Example 1 and Comparative Example 2 are as follows: Figure 4a -c. Among them, the tetracycline degradation rate of the simulated tetracycline wastewater of Example 1 at pH values of 3, 7 and 10 all reached more than 90%, while the tetracycline degradation rate of the simulated tetracycline wastewater of Comparative Example 1 was greatly affected by the pH value of the simulated tetracycline wastewater, and its highest tetracycline degradation rate did not reach 50%; the highest tetracycline degradation rate of the simulated tetracycline wastewater of Comparative Example 2 was less than 20%.
[0077] The experimental results of tetracycline degradation rate of simulated tetracycline wastewater corresponding to Example 1, Comparative Example 1 and Comparative Example 2 with different usage times are as follows: Figure 5a -c, when Example 1 was used for the eighth time, the tetracycline degradation rate of the simulated tetracycline wastewater at different pH values could still reach 90%, showing its excellent repeated stable electrocatalytic performance; the tetracycline degradation rates of Comparative Examples 1 and 2 decreased significantly with the increase in the number of repeated uses, and their repeated stable performance of electrocatalytic oxidation of tetracycline wastewater was poor.
[0078] According to the above experimental results, the copper-based Sm3Co5O foam prepared according to the present invention 12-x Se x The layer-loaded [Pb(CO)4]Se nanocrystalline anode material has excellent electrocatalytic degradation performance of tetracycline and excellent repeated stable degradation.
[0079] To illustrate in further detail, three additional examples are provided below.
[0080] Example 2
[0081] Preferred embodiment 2 of the present invention provides a method for preparing an anode material for electrocatalytic degradation of tetracycline wastewater, comprising the following steps performed in sequence:
[0082] Step [1] forms a (Sm-Co)2O6 compound layer on the surface of the copper foam substrate, specifically comprising the following operations:
[0083] a1. Add samarium tricyclopentadienide, samarium sulfate and didodecylamine to 3,5-dimethylaniline and mix well to form an additive solution having a samarium tricyclopentadienide concentration of 105 g / L, a samarium sulfate concentration of 272 g / L and a didodecylamine concentration of 30 g / L; add cobalt porphyrin, cobalt oxalate and sodium ethoxide to deionized water and mix well to form a base solution having a cobalt porphyrin concentration of 60 g / L, a cobalt oxalate concentration of 280 g / L and a sodium ethoxide concentration of 70 g / L; add the additive solution to the base solution in a volume ratio of 3:5 and mix well to form a water / organic reagent emulsion type Sm-Co co-deposition solution;
[0084] a2. The copper foam was immersed in the Sm-Co co-deposition solution (the weight of the copper foam immersed in each liter of the Sm-Co co-deposition solution was 150 g) and used as a cathode, stainless steel was used as an anode, and electrodeposition was performed at room temperature, wherein the electrodeposition voltage was a constant voltage of 1.8, and the electrodeposition time was 25 minutes to obtain a copper foam with a Sm-Co co-deposition layer formed on the surface, which was recorded as intermediate A;
[0085] a3. Sodium acetate, sodium ferric ethylenediaminetetraacetate and 69% nitric acid are added to deionized water to form an oxidizing solution with a sodium acetate concentration of 20 g / L, a sodium ferric ethylenediaminetetraacetate concentration of 60 g / L and a nitric acid mass percentage concentration of 1%, and the intermediate A is immersed in the oxidizing solution (the weight of the intermediate A immersed in each liter of the oxidizing solution is 40 g), and immersed at room temperature for 1.5 hours to obtain a foamed copper with a (Sm-Co)2O6 compound layer formed on the surface, which is recorded as intermediate B.
[0086] Step [2] The (Sm-Co)2O6 compound layer on the surface of the copper foam substrate is converted into Sm3Co5O by selenization substitution reaction. 12-x Sex Film layer, where 1≤x≤4; the specific operation is:
[0087] 350g of intermediate B was placed in an atmosphere protection furnace, and 120g of selenious acid and 80g of calcium selenide were added to the furnace. The reaction was carried out at 100°C for 4 hours under argon atmosphere to finally obtain intermediate C (with Sm3Co5O 12-x Se x Copper foam of the film layer);
[0088] Step [3] Sm3Co5O on the surface of the copper foam substrate 12-x Se x The [Pb(CO)4]Se nanocrystals are loaded on the film layer, specifically including the following operations:
[0089] c1. Tetraethyl lead, tert-butyl 3,5-dicarbonyl hexanoate and selenious acid were dissolved in ethanol to form an organic base liquid having a tetraethyl lead concentration of 140 mL / L, a tert-butyl 3,5-dicarbonyl hexanoate concentration of 420 g / L and a selenious acid concentration of 160 g / L; lead sulfate was added to deionized water to form an inorganic additive liquid having a lead sulfate concentration of 100 g / L; a certain amount of inorganic additive liquid was added to the organic base liquid (the volume ratio between the organic base liquid and the inorganic additive liquid was 2: 5) to form a crystallization liquid;
[0090] c2. The intermediate C is immersed in the crystallization solution (the weight of the intermediate C immersed in each liter of the crystallization solution is 220 g), and reacted in a reactor at 40 ° C for 16 hours to form Sm3Co5O on the surface of the foam copper base. 12-x Se x The film layer is loaded with [Pb(CO)4]Se nanocrystals, and finally the anode material (foam copper-based Sm3Co5O 12-x Se x layer loaded with [Pb(CO)4]Se nanocrystals).
[0091] Example 3
[0092] Preferred embodiment 3 of the present invention provides a method for preparing an anode material for electrocatalytic degradation of tetracycline wastewater, comprising the following steps performed in sequence:
[0093] Step [1] forms a (Sm-Co)2O6 compound layer on the surface of the copper foam substrate, specifically comprising the following operations:
[0094] a1. Add samarium tricyclopentadienide, samarium sulfate and didodecylamine to 3,5-dimethylaniline and mix well to form an additive solution having a samarium tricyclopentadienide concentration of 140 g / L, a samarium sulfate concentration of 320 g / L and a didodecylamine concentration of 60 g / L; add cobalt porphyrin, cobalt oxalate and sodium ethoxide to deionized water and mix well to form a base solution having a cobalt porphyrin concentration of 110 g / L, a cobalt oxalate concentration of 160 g / L and a sodium ethoxide concentration of 10 g / L; add the additive solution to the base solution in a volume ratio of 1:7 and mix well to form a water / organic reagent emulsion type Sm-Co co-deposition solution;
[0095] a2. The copper foam was immersed in the Sm-Co co-deposition solution (the weight of the copper foam immersed in each liter of the Sm-Co co-deposition solution was 210 g) and used as a cathode, stainless steel was used as an anode, and electrodeposition was performed at room temperature, wherein the electrodeposition voltage was a constant voltage of 2.5 V, and the electrodeposition time was 8 minutes to obtain a copper foam with a Sm-Co co-deposition layer formed on the surface, which was recorded as intermediate A;
[0096] a3. Sodium acetate, sodium ferric ethylenediaminetetraacetate and 69% nitric acid by mass are added to deionized water to form an oxidizing solution with a sodium acetate concentration of 40 g / L, a sodium ferric ethylenediaminetetraacetate concentration of 90 g / L and a nitric acid mass percentage concentration of 5%, and the intermediate A is immersed in the oxidizing solution (the weight of the intermediate A immersed in each liter of the oxidizing solution is 80 g), and immersed at room temperature for 3 hours to obtain a foamed copper with a (Sm-Co)2O6 compound layer formed on the surface, which is recorded as intermediate B.
[0097] Step [2] The (Sm-Co)2O6 compound layer on the surface of the copper foam substrate is converted into Sm3Co5O by selenization substitution reaction. 12-x Se x Film layer, where 1≤x≤4; the specific operation is:
[0098] 850g of intermediate B was placed in an atmosphere protection furnace, and 190g of selenious acid and 210g of calcium selenide were added to the furnace. The reaction was carried out at 80°C for 7 hours under argon atmosphere to finally obtain intermediate C (with Sm3Co5O 12-x Se x Copper foam of the film layer);
[0099] Step [3] Sm3Co5O on the surface of the copper foam substrate 12-x Se x The [Pb(CO)4]Se nanocrystals are loaded on the film layer, specifically including the following operations:
[0100] c1. Tetraethyl lead, tert-butyl 3,5-dicarbonyl hexanoate and selenous acid were dissolved in ethanol to form an organic base liquid having a tetraethyl lead concentration of 290 mL / L, tert-butyl 3,5-dicarbonyl hexanoate concentration of 580 g / L and a selenous acid concentration of 190 g / L; lead sulfate was added to deionized water to form an inorganic additive liquid having a lead sulfate concentration of 100 g / L; a certain amount of the inorganic additive liquid was added to the organic base liquid (the volume ratio between the organic base liquid and the inorganic additive liquid was 2:3) to form a crystallization liquid;
[0101] c2. The intermediate C is immersed in the crystallization solution (the weight of the intermediate C immersed in each liter of the crystallization solution is 246 g), and reacted in a reactor at 75 ° C for 12 hours to form Sm3Co5O on the surface of the foam copper base. 12-x Se x The film layer is loaded with [Pb(CO)4]Se nanocrystals, and finally the anode material (foam copper-based Sm3Co5O 12-x Se x layer loaded with [Pb(CO)4]Se nanocrystals).
[0102] Example 4
[0103] Preferred embodiment 4 of the present invention provides a method for preparing an anode material for electrocatalytic degradation of tetracycline wastewater, comprising the following steps performed in sequence:
[0104] Step [1] forms a (Sm-Co)2O6 compound layer on the surface of the copper foam substrate, specifically comprising the following operations:
[0105] a1. Add samarium tricyclopentadienide, samarium sulfate and didodecylamine to 3,5-dimethylaniline and mix well to form an additive solution having a samarium tricyclopentadienide concentration of 116 g / L, a samarium sulfate concentration of 295 g / L and a didodecylamine concentration of 45 g / L; add cobalt porphyrin, cobalt oxalate and sodium ethoxide to deionized water and mix well to form a base solution having a cobalt porphyrin concentration of 85 g / L, a cobalt oxalate concentration of 220 g / L and a sodium ethoxide concentration of 40 g / L; add the additive solution to the base solution in a volume ratio of 2:7 and mix well to form a water / organic reagent emulsion type Sm-Co co-deposition solution;
[0106] a2. The copper foam was immersed in the Sm-Co co-deposition solution (the weight of the copper foam immersed in each liter of the Sm-Co co-deposition solution was 180 g) and used as a cathode, stainless steel was used as an anode, and electrodeposition was performed at room temperature, wherein the electrodeposition voltage was a constant voltage of 2.2 V, and the electrodeposition time was 18 minutes to obtain a copper foam with a Sm-Co co-deposition layer formed on the surface, which was recorded as intermediate A;
[0107] a3. Sodium acetate, sodium ferric ethylenediaminetetraacetate and 69% nitric acid by mass are added to deionized water to form an oxidizing solution with a sodium acetate concentration of 30 g / L, a sodium ferric ethylenediaminetetraacetate concentration of 75 g / L and a nitric acid mass percentage concentration of 3%, and the intermediate A is immersed in the oxidizing solution (the weight of the intermediate A immersed in each liter of the oxidizing solution is 60 g), and immersed at room temperature for 2.2 hours to obtain a foamed copper with a (Sm-Co)2O6 compound layer formed on the surface, which is recorded as intermediate B.
[0108] Step [2] The (Sm-Co)2O6 compound layer on the surface of the copper foam substrate is converted into Sm3Co5O by selenization substitution reaction. 12-x Se x Film layer, where 1≤x≤4; the specific operation is:
[0109] 600g of intermediate B was placed in an atmosphere protection furnace, and 155g of selenious acid and 145g of calcium selenide were added to the furnace. The reaction was carried out at 90°C for 6 hours under argon atmosphere to finally obtain intermediate C (with Sm3Co5O 12-x Se x Copper foam of the film layer);
[0110] Step [3] Sm3Co5O on the surface of the copper foam substrate 12-x Se x The [Pb(CO)4]Se nanocrystals are loaded on the film layer, specifically including the following operations:
[0111] c1. Tetraethyl lead, tert-butyl 3,5-dicarbonyl hexanoate and selenious acid were dissolved in ethanol to form an organic base liquid having a tetraethyl lead concentration of 215 mL / L, a tert-butyl 3,5-dicarbonyl hexanoate concentration of 500 g / L and a selenious acid concentration of 175 g / L; lead sulfate was added to deionized water to form an inorganic additive liquid having a lead sulfate concentration of 115 g / L; a certain amount of the inorganic additive liquid was added to the organic base liquid (the volume ratio between the organic base liquid and the inorganic additive liquid was 2:3) to form a crystallization liquid;
[0112] c2. The intermediate C is immersed in the crystallization solution (the weight of the intermediate C immersed in each liter of the crystallization solution is 235g), and reacted in a reactor at 55°C for 14 hours to form Sm3Co5O on the surface of the foam copper base. 12-x Se x The film layer is loaded with [Pb(CO)4]Se nanocrystals, and finally the anode material (foam copper-based Sm3Co5O 12-x Se x layer loaded with [Pb(CO)4]Se nanocrystals).
[0113] The above are only preferred embodiments of the present invention. It should be understood that the description of the above embodiments is only used to help understand the method and core ideas of the present invention, and is not used to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, etc. made within the ideas and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing an anode material for electrocatalytic degradation of tetracycline wastewater, characterized in that: It contains the following steps in order: Step [1] forms a (Sm-Co)2O6 compound layer on the surface of the copper foam substrate, specifically comprising the following operations: a1. Add samarium tricyclopentadienide, samarium sulfate and didodecylamine to 3,5-dimethylaniline and mix well to form an additive solution; add cobalt porphyrin, cobalt oxalate and sodium ethoxide to deionized water and mix well to form a base solution; add a certain amount of the additive solution to the base solution and mix well to form an emulsified Sm-Co co-deposition solution; a2. The copper foam is immersed in the Sm-Co co-deposition solution and used as a cathode, stainless steel is used as an anode, and electrodeposition is performed at room temperature to obtain a copper foam having a Sm-Co co-deposition layer formed on the surface, recorded as intermediate A; a3. Sodium acetate, sodium ferric ethylenediaminetetraacetate and nitric acid having a mass fraction concentration of 69% are added to deionized water to form an oxidizing solution, and the intermediate A is immersed in the oxidizing solution for 1.5 to 3 hours at room temperature to obtain a foam copper having a (Sm-Co)2O6 compound layer formed on the surface, which is recorded as intermediate B; Step [2] The (Sm-Co)2O6 compound layer on the surface of the copper foam substrate is converted into Sm3Co5O by selenization substitution reaction. 12- x Se x Film layer, where 1≤x≤4; the specific operation is: The intermediate B is placed in an atmosphere protection furnace, and a certain amount of selenious acid and calcium selenide are added to the furnace, and reacted at 80-100° C. for 4-7 hours under argon atmosphere to finally obtain the intermediate C; Step [3] Sm3Co5O on the surface of the copper foam substrate 12-x Se x The [Pb(CO)4]Se nanocrystals are loaded on the film layer, specifically including the following operations: c1. Dissolve tetraethyl lead, tert-butyl 3,5-dicarbonylhexanoate and selenious acid in ethanol to form an organic base liquid; add lead sulfate to deionized water to form an inorganic additive liquid; add a certain amount of the inorganic additive liquid to the organic base liquid to form a crystallization liquid; c2. Immersing the intermediate C into the crystallization solution, reacting in a reactor at 40-75° C. for 12-16 hours, and finally obtaining the anode material.
2. The method for preparing an anode material for electrocatalytic degradation of tetracycline wastewater according to claim 1, characterized in that: The concentration of samarium tricyclopentadienide in the additive liquid in step a1 is 105g / L-140g / L, the concentration of samarium sulfate is 270g / L-320g / L, and the concentration of didodecylamine is 30g / L-60g / L; the concentration of cobalt porphyrin in the base liquid is 60g / L-110g / L, the concentration of cobalt oxalate is 160g / L-280g / L, and the concentration of sodium ethoxide is 10g / L-70g / L; the volume ratio between the additive liquid and the base liquid of the Sm-Co co-deposition solution is 1-3:5-8.
3. The method for preparing an anode material for electrocatalytic degradation of tetracycline wastewater according to claim 1, characterized in that: In step a2, the weight of the foamed copper immersed in each liter of the Sm-Co co-deposition solution is 150-210 g; the voltage of the electrodeposition is a constant voltage of 1.8-2.5 V, and the electrodeposition time is 8-25 minutes.
4. The method for preparing an anode material for electrocatalytic degradation of tetracycline wastewater according to claim 1, characterized in that: In step a3, the sodium acetate concentration of the oxidizing solution is 20g / L-40g / L, the sodium ferric ethylenediaminetetraacetate concentration is 60g / L-90g / L, and the mass percentage concentration of nitric acid is 1%-5%; the weight of the intermediate A immersed in each liter of the oxidizing solution is 40-80g.
5. The method for preparing an anode material for electrocatalytic degradation of tetracycline wastewater according to claim 1, characterized in that: The added amounts of selenous acid and calcium selenide corresponding to every 350g-850g of intermediate B are 120g-190g and 80g-210g respectively.
6. The method for preparing an anode material for electrocatalytic degradation of tetracycline wastewater according to claim 1, characterized in that: In step c1, the tetraethyl lead concentration of the organic base liquid is 140 mL / L-290 mL / L, the tert-butyl 3,5-dicarbonylhexanoate concentration is 420 g / L-580 g / L, and the selenious acid concentration is 160 g / L-190 g / L; the lead sulfate concentration of the inorganic additive liquid is 100 g / L-130 g / L; and the volume ratio between the organic base liquid and the inorganic additive liquid of the crystallization liquid is 1-2:3-5.
7. The method for preparing an anode material for electrocatalytic degradation of tetracycline wastewater according to claim 1, characterized in that: In step c2, the weight of the intermediate C immersed in each liter of the crystallization solution is 220-250 g.
Citation Information
Patent Citations
Pd / foamy copper electrode and preparation method and application thereof
CN107557770A
Method for electro-catalytic degradation of tetracycline in water
CN110589935A
Novel foamy copper composite electrode and preparation method and application thereof
CN117142587A
Molybdenum-doped cuprous selenide electrocatalyst with high methane adsorption selenium defect as well as preparation method and application of molybdenum-doped cuprous selenide electrocatalyst
CN117448847A
Anode material for photoelectric degradation of tetracycline, and preparation method therefor
WO2023082384A1